Improving the quality of consent to randomised controlled trials by using continuous consent and clinician training in the consent process. Issue 8 (28th July 2006) - Allmark, P; Mason, S
Abstract : Objective: To assess whether continuous consent, a process in which information is given to research participants at different stages in a trial, and clinician training in that process were effective when used by clinicians while gaining consent to the Total Body Hypothermia (TOBY) trial. The TOBY trial is a randomised controlled trial (RCT) investigating the use of whole-body cooling for neonates with evidence of perinatal asphyxia. Obtaining valid informed consent for the TOBY trial is difficult, but is a good test of the effectiveness of continuous consent. Methods: Semistructured interviews were conducted with 30 sets of parents who consented to the TOBY trial and with 10 clinicians who sought it by the continuous consent process. Analysis was focused on the validity of parental consent based on the consent components of competence, information, understanding and voluntariness. Results: No marked problems with consent validity at the point of signature were observed in 19 of 27 (70%) couples. Problems were found mainly to lie with the competence and understanding of the parents: mothers, particularly, had problems with competence in the early stages of consent. Problems in understanding were primarily to do with side effects. Problems in both competence and understanding were observed to reduce markedly, particularly for mothers, in the post-signature phase, when further discussion took place. Randomisation was generally understood but unpopular. Information was not always given by clinicians in stages during the short period available before parents gave consent. Most clinicians, however, were able to give follow-up information. Discussion: Consent validity was found to compare favourably with similar trials examined in the Euricon study. Conclusion: Adopting the elements of the continuous consent process and clinician training in RCTs should be considered by researchers, particularly when they have concerns about the quality of consent they are likely to obtain by using a conventional process.